The impact of sex, age and training on biventricular cardiac adaptation in healthy adult and adolescent athletes: Cardiac magnetic resonance imaging study. (29th August 2020) - Csecs, Ibolya; Czimbalmos, Csilla; Toth, Attila; Dohy, Zsofia; Suhai, Imre F; Szabo, Liliana; Kovacs, Attila; Lakatos, Balint; Sydo, Nora; Kheirkhahan, Mobin; Peritz, David; Kiss, Orsolya; et al.
Abstract: Aims: Physiological cardiac adaptation in athletes is influenced by multiple factors. This study aimed to investigate the impact of sex, age, body size, sports type and training volume on cardiac adaptation in healthy athletes with cardiac magnetic resonance imaging. Methods: A total of 327 athletes (242 male) were studied (adults ≥18 years old; adolescents 14–18 years old). Left and right ventricular ejection fractions, end-diastolic volume, end-systolic volume, stroke volumes and masses were measured. Left ventricular end-diastolic volume/left ventricular mass, right ventricular end-diastolic volume/right ventricular mass and derived right/left ventricular ratios were determined to study balanced ventricular adaptation. Athletes were categorised as skill, power, mixed and endurance athletes. Results: Male athletes had higher left and right ventricular volumes and masses in both adult ( n = 215 (145 male); 24 ± 5 years old) and adolescent ( n = 112 (97 male); 16 ± 1 years old) groups compared with women (all P < 0.05). In adults, male sex, age, body surface area, weekly training hours, mixed and endurance sports correlated with higher ventricular volumes and masses (all P < 0.05); and a combination of age, sex, training hours, endurance and mixed sports explained 30% of the variance of the left ventricular end-diastolic volume index ( r = 0.30), right ventricular end-diastolic volume index ( r = 0.34), right ventricular mass index ( r = 0.30); and as much as 53% of the left ventricular mass index ( r = 0.53) (all P < 0.0001). In adolescents, positive correlations were found between training hours and left ventricular hypertrophy ( r = 0.39, P < 0.0001), and biventricular dilation (left ventricular end-diastolic volume r = 0.34, P = 0.0008; right ventricular end-diastolic volume r = 0.36, P = 0.0004). In adolescents, age and body surface area did not correlate with cardiac magnetic resonance parameters. Conclusion: There are significant sex differences in the physiological adaptation of adult and adolescent athlete's heart; and male sex, higher training volume and endurance sports are major determinants of sports adaptation in adults.